NRN1 interacts with Notch to increase oncogenic STAT3 signaling in melanoma - Devitt, Lucia; Westphal, Dana; Pieger, Katharina; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Cell Communication and Signaling, 2024)
Background: Melanoma is a highly heterogeneous cancer, in which frequent changes in activation of signaling pathways lead to a high adaptability to ever changing tumor microenvironments. The elucidation of cancer specific signaling pathways is of great importance, as demonstrated by the inhibitor of the common BrafV600E mutation PLX4032 in melanoma treatment. We therefore investigated signaling pathways that were influenced by neurotrophin NRN1, which has been shown to be upregulated in melanoma. Methods: Using a cell culture model system with an NRN1 overexpression, we investigated the influence of NRN1 on melanoma cells’ functionality and signaling. We employed real time cell analysis and spheroid formation assays, while for investigation of molecular mechanisms we used a kinase phosphorylation kit as well as promotor activity analysis followed by mRNA and protein analysis. Results: We revealed that NRN1 interacts directly with the cleaved intracellular domain (NICD) of Notch1 and Notch3, causing a potential retention of NICD in the cytoplasm and thereby reducing the expression of its direct downstream target Hes1. This leads to decreased sequestration of JAK and STAT3 in a Hes1-driven phosphorylation complex. Consequently, our data shows less phosphorylation of STAT3 while presenting an accumulation of total protein levels of STAT3 in association with NRN1 overexpression. The potential of the STAT3 signaling pathway to act in both a tumor suppressive and oncogenic manner led us to investigate specific downstream targets – namely Vegf A, Mdr1, cMet - which were found to be upregulated under oncogenic levels of NRN1. Conclusions: In summary, we were able to show that NRN1 links oncogenic signaling events between Notch and STAT3 in melanoma. We also suggest that in future research more attention should be payed to cellular regulation of signaling molecules outside of the classically known phosphorylation events. Graphical Abstract: (Figure presented.).
CRIS-Team Scopus Importer:2024-05-10
Keywords: Melanoma; Notch; NRN1; STAT3

Nuclear AREG affects a low-proliferative phenotype and contributes to drug resistance of melanoma - Seefried, Felix; Haller, Lucia; Fukuda, Shinji; Thongmao, Aranya; Schneider, Nadja; Utikal, Jochen; Higashiyama, Shigeki; Boßerhoff, Anja Katrin; Kuphal, Silke (International Journal of Cancer, 2022)
AMPHIREGULIN (AREG) is a multifaceted molecule, which acts not only as an extracellular ligand for EGF receptor (EGFR), but also as an intracellular signaling molecule. It remains elusive, however, whether AREG has a tumor suppressive or oncogenic role in melanoma. Here, we found that several melanoma cell lines express AREG, but the expression does not correlate with that of EGFR. Recombinant AREG and the neutralizing antibody experiments showed that intracellular AREG plays an important role in melanoma, implying a divergent function of AREG in addition to the role as a ligand for EGFR. Further investigation of this mechanism revealed that particularly nuclear-localized AREG regulates IGF-1R, P21 (Cip1/Waf1), TP53 and JARID1B protein accumulation in the nucleus. Furthermore, manipulation of nuclear AREG levels has influence on heterochromatin condensation (HP1beta, SETDB1) and trimethylation of histones H3K9 and H3K4. As these molecules correspond to previously identified markers for slow-cycling drug resistant cells, we speculate that nuclear AREG predisposes cells to resistance to therapy. According to the hypothesis, we detected the accumulation of AREG in the nucleus of SK-Mel-28-VR, which was cultured under Vemurafenib (VR) selection pressure, and this correlates with JARID1B expression. Here, knockdown of AREG makes the previously resistant cells more sensitive to VR treatment, resulting in inhibited proliferation. Taken together, we suggest that nuclear AREG affects a slow-cycling phenotype and increases resistance to VR, raising a possibility that AREG might be a potential therapeutic target for resistance in melanoma.
CRIS-Team WoS Importer:2022-09-16

The Role of NRN1 in the Development and Progression of malignant Melanoma - Haller, Lucia; Reichelt, Judith; Boßerhoff, Anja Katrin; Kuphal, Silke (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24